Digital Security Adoption in Smart Lock Systems: A Systematic Literature Review Based on the Diffusion of Innovations Theory - Zumara, Muzammil; Malahayati, Malahayati; Ahmadian, Hendri (Jurusan Pendidikan Teknik Elektro, 2026)
The rapid development of Internet of Things (IoT) technology has transformed traditional residential security into an interconnected smart home ecosystem, where smart locks function as key devices for digital access control. However, despite growing market penetration, their adoption remains constrained by concerns related to security perception and user trust. This study analyzes the adoption of digital security in smart locks using the perspective of Diffusion of Innovations theory through a Systematic Literature Review (SLR) approach following the PRISMA Protocol. Literature was collected from IEEE Xplore, Scopus, ScienceDirect, and Google Scholar covering the 2019–2025 period, resulting in 25 selected studies. The synthesis indicates that relative advantage and compatibility act as the primary drivers of adoption, while technical complexity and cybersecurity risks represent major barriers. In addition, user trust is identified as a critical mediating factor influencing adoption decisions. Nevertheless, several limitations should be noted. The abstract does not clearly specify the inclusion and exclusion criteria applied during the literature selection process, which reduces methodological transparency. Moreover, although the number of analyzed articles is stated, the dominant research design whether qualitative, quantitative, or experimental is not explained, limiting the reader’s ability to evaluate the strength of the evidence. Consequently, while the findings highlight practical implications such as improving interoperability through protocols like Matter and strengthening user education to reduce perceived risks, the conclusions should be interpreted cautiously within the scope of the review.